Arahan Lokasi Potensial Pasar Tradisional di Kota Baubau - Liza Hardiyanti Hasiu; Arifuddin Akil; Wiwik Wahidah Osman (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Traditional markets experience a decline of 8% annually while the modern market actually grows 31.4% annually. Along with increasing population, the demand for easily accessible markets with all aspects is important to develop. Oleh karena itu, perlu menyediakan lokasi pasar tradisional yang potensial dan menarik. The purpose of this study is to identify conditions and patterns of distribution, determine potential locations and directives for the development of traditional market facilities in Baubau City. The method used in this study is the analysis of the nearest neighbor (neighbor analysis) and spatial analysis showing grid-based GIS applications. The results of the analysis determine the potential location, then the direction of the development of traditional market facilities is formulated. The results of this study are the first distribution patterns of traditional markets in the city of Baubau classified as random, both locations are very potential traditional markets located in the middle of the city which is the location of the Baubau City activity center, while for potential locations and not potential to spread randomly throughout the city , thirdly there are 3 points of development direction for potential locations to be used as traditional markets which are located in Kecamatan Bungi Kelurahan Ngkari-ngkari, Kecamatan Wolio Kelurahan Kadolokatapi, and Kecamatan Betoambari Kelurahan Sula.